Evolution of milk production systems in Tropical Latin America and its interrelationship with markets : An analysis of the Colombian case - Holmann, Federico J.; Rivas Ríos, Libardo; Carulla, Juan E.; Rivera, B.; Giraldo, Luis Alfonso; Guzmán Pérez, Silvio; Martínez, M.; Medina, A.; Farrow, Andrew (2003)
The objectives were to: (1) identify and quantify the effect of technological change on productivity, profitability, and competitiveness in different milk production systems and regions of the country; (2) analyze the relationship between productivity, technological change, profitability, and competitiveness; (3) analyze the evolution of milk production systems in Colombia; and (4) discuss the market concentration and its impact on the formation of milk price. Data came from a survey to 545 farms during the year 2000 in five regions: Caribbean and Piedmont in the lowlands, Coffee Growing, Antioquia, and the Cundiboyacense altiplanicie in the highlands. The survey was designed to quantify inputs and products in order to determine costs and prices at the farm level in order to calculate (a) variable costs for feed supplementation, labor, health, reproduction, fertilization, and irrigation; (b) gross income from the sale of milk and beef, and (c) to characterize farms according to productivity level and management practices. The statistical analysis of multiple correspondence and general linear models were used to explain the variability observed between productivity and profitability as a function of technological change.